Rapid synthesis of SiC powders by spark plasma-assisted carbothermal reduction reaction. Issue 6 (15th April 2017) - Wang, Fengfeng; Xiang, Daoping; Wang, Yuwu; Li, Jianbao
Abstract: The SiC powders were rapidly synthesized by spark plasma-assisted carbothermal reduction (SPCR) at low temperature using quartz sand, carbon black and phenolic resin as raw materials. The effects of synthesis temperature on the phase transformation and microstructure of the product powders were investigated. The SiC powders were characterized by X-ray diffraction, scanning electron microscopy, particle size and surface area analyses. Experimental results showed that the quartz sands were completely converted to fine SiC powders at 1800 °C for 5 min. The obtained SiC powders with narrow and uniform particle size distribution showed an approximately spherical shape. Quantitative phase-composition analysis using the Rietveld method demonstrated that the synthesized SiC particles had a cubic sphalerite structure with a F 4 ¯ 3 m space group and the samples were composed of relatively high content of SiC phase.